The Concept of Tolerance in Western Civilization in the Perspective of the Quran and Hadith: A Comparative Analysis - Kharis Nugroho; Apriantoro, Muhamad Subhi; Ahmad Hermawan; Miftah Khilmi Hidayatullah (Ethica: International Journal of Humanities and Social Science Studies, 2023)
This study aims to explain the concept of tolerance practiced by Western societies in the perspective of the Qur'an and Hadith . This research used techniques of content analysis and library research to analyze the data and interpret its meaning since the researcher relies heavily on documents as the main sources of information. From this research it is concluded that the formation of the pattern of tolerance doctrine between Islam and the West is very different. The doctrine of tolerance in Islam is not shaped by history, but is an integral part of the Islamic heritage. Unlike the West, whose doctrine of tolerance is shaped by history due to abuse of power. That is why equating the Islamic doctrine of tolerance with the doctrine of tolerance in the West is incorrect.